PENGARUH SUHU DAN LAMA PENGERINGAN TERHADAP SIFAT KIMIA DANORGANOLEPTIK TEPUNG UMBI TALAS (Colocasia esculenta) - Erni, Nurfiani; Kadirman, Kadirman; Fadilah, Ratnawaty (Jurnal Pendidikan Teknologi Pertanian, 2018)
This  study  aims  at  knowing  the  influence  of  temperature  and  leght  of  drying  to chemical characteristic and organoleptic of taro flour. This study is an experimental study using complete random design, factorial pattern which is consisted of two factors namely: drying temperature (P1 = 50 0C, and P2= 60 0C) and length of drying (T1 = 8 hours, and T2 = 10 hours) with  three  time  repetition.  Variables  observed  were  rendamen,  the  content  of  water, the content of ashes, the content of protein, the content of carbohydrate, the appearance, the smell and texture. Analysis technic used ini this study were analysis of variance (ANOVA) and Duncan advanced  test which were calculated through software statistical package for social science (SPSS) version 21.0. The results showed that temperature and length of drying had an evident influence to the chemical characteristic and organoleptic of taro flour. The results of the chemical characteristic and organoleptic of taro flour covered 8,57 % rendamen, 11,80 % water, 11,46 % ashes, 5,95 % protein, 73,58 % carbohydrate,  8,60 % in appearance, 6,82 % in smell, and  7,20 % in texture